PENERAPAN STRATEGI BELAJAR AKTIF TIPE INDEX CARD MATCH TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 1 SIPORA KABUPATEN KEPULAUAN MENTAWAI TAHUN PELAJARAN 2013/2014 - Palmira, Palmira; Aima, Zulfitri; Yuliana Fitri, Dewi (Pendidikan Matematika, 2014)
Â ABSTRACTÂ This research was intended to reveal whether the mathematics conceptual understanding of the students taught by using Index Card Match active learning strategy was better than that of students taught by using conventional learning. This was an experimental research which used random toward the subject design. The population of this research was all of students in class VII of SMPN 1 Sipora Kabupaten Kepulauan Mentawai registered in academic year 2013/2014. The instrument of the research was an essay test of 12 items whose reliability was 0,795. The data gathered was analyzed by using normality test, homogeneity test and t-test. Based on the result of data analysis it was found that the mathematics conceptual understanding of the students taught by using Index Card Match active learning strategy was better than that of students taught by using conventional learning in class VII of SMPN 1 Sipora Kabupaten Kepulauan Mentawai.